2017
DOI: 10.1063/1.4977905
|View full text |Cite
|
Sign up to set email alerts
|

New scheme for enhancement of maximum proton energy with a cone-hole target irradiated by a short intense laser pulse

Abstract: Improvement of proton energy from short intense laser interaction with a new proposal of a cone-hole target is investigated via two-dimensional particle-in-cell simulations. The configuration of the target is a cone structure with a hole of changeable diameter through the center of the tip, with proton layers contaminated both on the target rear surface and at the rear part of the hole. In the interacting process, the cone-hole geometry enables the focus of the laser pulse by the cone structure and the consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Some works showed that the interaction of the ultra-high intensity laser pulse with a micro-cone target can generate protons accelerated at energies of tens of MeV with low angular divergence and high laser absorption [9][10][11][12] in the Target Normal Sheath Acceleration and Direct laser-lightpressure regimes. Other papers were devoted to different kinds of cone targets suitable for proton acceleration at energies up to few tens of MeV [13][14][15][16][17][18]. A new experiment at Vulcan facility shows that the interaction of the ultra-high intensity laser pulse with a ultra-thin foil can generate protons accelerated at energies exceeding 94 MeV [19].…”
Section: Introductionmentioning
confidence: 99%
“…Some works showed that the interaction of the ultra-high intensity laser pulse with a micro-cone target can generate protons accelerated at energies of tens of MeV with low angular divergence and high laser absorption [9][10][11][12] in the Target Normal Sheath Acceleration and Direct laser-lightpressure regimes. Other papers were devoted to different kinds of cone targets suitable for proton acceleration at energies up to few tens of MeV [13][14][15][16][17][18]. A new experiment at Vulcan facility shows that the interaction of the ultra-high intensity laser pulse with a ultra-thin foil can generate protons accelerated at energies exceeding 94 MeV [19].…”
Section: Introductionmentioning
confidence: 99%
“…© 2018 Author (s) In recent years, the laser-plasma interactions have been developing rapidly with the advance in the laser technology. The generation and transportation of fast electrons in dense plasmas have attracted much attention due to the potential applications in the fast ignition (FI) of inertial confinement fusion (ICF), 1,2 ion acceleration, [3][4][5] and laboratory astrophysics, 6 and so on. In order to fulfill these applications, it is critical to not only generate but also control such beams appropriately, such as collimating and guiding them over certain distances.…”
mentioning
confidence: 99%